Residential mobility patterns of the elderly household in South Korea - HAN, Sangsuk (KDI School, 2016)
The purpose of this study is to examine prefer residential of the elderly and the effects of the elderly household characteristics on their residential mobility to estimate housing demand of the elderly. This study uses Korea Labor Institute Panel Data and Logit and Regression model. The analysis results show that age, health and employment status effects on the elderly’s residential mobility, the older, unhealthier, working elderly tend to move to rural regions.
Thesis(Master) --KDI School:Master of Public Policy,2016